2018
DOI: 10.1002/mds.27303
|View full text |Cite
|
Sign up to set email alerts
|

Are the MDS‐UPDRS–Based Composite Scores Clinically Applicable?

Abstract: Our findings support the application of various MDS-UPDRS-based composite scores. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…This is in line with findings examining the old UPDRS scale [28]. Although several studies have suggested that composite scores are able to detect clinically relevant differences over time [26,27,29], the authors of the new scale clearly recommended against the use of I-III composite scores as their unequal factorial loading reduces sensitivity to change [17].…”
Section: Challenge 2: Outcome Measures Motor Progressionsupporting
confidence: 77%
See 2 more Smart Citations
“…This is in line with findings examining the old UPDRS scale [28]. Although several studies have suggested that composite scores are able to detect clinically relevant differences over time [26,27,29], the authors of the new scale clearly recommended against the use of I-III composite scores as their unequal factorial loading reduces sensitivity to change [17].…”
Section: Challenge 2: Outcome Measures Motor Progressionsupporting
confidence: 77%
“…However, changes in the MDS-UPDRS total score (within the first five years of disease) are largely driven by changes in the MDS-UPDRS Part III score; as part I and II score changes are not as pronounced over time [26] their addition into a total score may reduce sensitivity to change [27]. This is in line with findings examining the old UPDRS scale [28].…”
Section: Challenge 2: Outcome Measures Motor Progressionsupporting
confidence: 69%
See 1 more Smart Citation
“…The questionnaire ( Supplementary file ) consisted of Part I, Part II, Part III, and Part IV. Part I pertained to patient characteristics, including demographic data (age, gender, educational level, occupation) and the main clinical features of PD (PD disease course, number of anti-PD drugs, Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) [ 20 ], and Hoehn & Yahr Stage (H & Y) [ 21 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Although Mestre et al [11] demonstrated that a 2.32-point change on the clinician-rated UDysRS Part 3 is the threshold for clinical relevance, the MCID estimates for the historic parts of the UDysRS have not yet been calculated. Although our team evaluated the MCID thresholds for Parts I [12], II [12], III [13], and the total score [14] of the MDS-UPDRS, the size of the minimally required change on the MDS-UPDRS MC is still unknown.…”
Section: Introductionmentioning
confidence: 99%